Investigating the potential of polysulfides obtained via inverse vulcanization as sustainable fertilizers - Valle, Stella Fortuna do (2022)
Global food security is one of the biggest challenges we face today, and to this end, establishing sustainable strategies towards the development of more efficient and safer agricultural products is indispensable. Sulfur (S) plays an important agronomic role for crops as a secondary macronutrient, and its deficiency in agricultural soils has become an increasing problem for crop productivity and quality. Elemental sulfur (S8) is an abundant byproduct of petroleum refining that stands out as a S-fertilizer. However, S8 can only be assimilated by plants after oxidation by soil microorganisms to sulfate, a slow process that restricts its agronomic efficiency, especially when applied as pellets. Aiming to optimize this conversion, we recently investigated the transformation of the stable S8 structure into a new material with linear S chains using the polymerization technique of inverse vulcanization. The polysulfides (PolyS) showed superior oxidation rates to S8, in addition to interesting processing and conformation characteristics, ideal for the incorporation of other fertilizers. Thus, the primary goal of this work was to evaluate the potential of PolyS as a versatile material with high efficiency as a multifunctional sulfur fertilizer. PolyS pellets were prepared with added porosity to the structure, aiming to increase the surface area for biological oxidation. A study was conducted to understand the interaction of this system with the bacterium Acidithiobacillus thiooxidans, which obtains energy from S oxidation. Moreover, compared to commercial S8 pellets, oxidation in soil was significantly higher from the combined application of the porous PolyS with bacterium. PolyS was also investigated as a dispersant matrix for the controlled-release of other fertilizers, with the advantage of serving as a rich source of S for plants. Composites containing sustainable phosphorus (P) sources with different solubility profiles - phosphate rock and struvite - were synthesized to study the physical and chemical effects of PolyS as a matrix. A synergistic effect between PolyS oxidation and phosphate release was verified, with the local acidity of sulfate generation favoring phosphorus solubilization. The application of PolyS-struvite composites for soybean cultivation was then tested in a greenhouse, with a systematic study of fertilizer effects on root profile and plant development. Compared to conventional soluble sources, PolyS led to higher sulfur uptake efficiency, and the controlled release of P stimulated the production of fine soybean roots. Based on the results it could be concluded that the polysulfides offer versatility for the design of different fertilizer products, with added value as an efficient S source.